Os movimentos de formação docente no projeto orientador de atividade - Borowsky, Halana Garcez (2017)
The present study is bound up to Programa de Pós-Graduação em Educação of Universidade Federal de Santa Maria (UFSM), in the research line "LP1 - Formação, Saberes e Desenvolvimento Profissional”. The main purpose was to investigate the essential relations of the teacher training movement in Clube de Matemática project – based on the perspective of Historical-Cultural Theory. CluMat/UFSM project, which began as an extension action focused on students from initial years, has been constituted as a formative space for its participants. This research was conducted based on the Cultural-Historical Theory (Vigotsky), Activity Theory (Leontiev) and Teaching-Orienting Activities (Moura). Accordingly, the applied methodology is described by the structure of the activity, which presents the need, reason, actions and procedures which were constituted during the development of the research. The production of the data occurred from the monitoring of the work of Clube de Matemática/UFSM, in 2015. The participants of this research were undergraduate students, teachers of basic education and collaborators who are part of the project. The data are presented based on what Moura (2002) defines as training episodes, which constitute the units of analysis (VYGOTSKY, 1991), which were delimited by the theory that this research was based. A question was raised: “What are the essential relationships of the teacher training movement in a project?". This question triggered three units of analysis - which aimed to represent the totality of what constitutes a guiding project of activity. – in other words: scientific knowledge, organization of teaching and human development. Based on this research, it is confirmed that a guiding project of teacher training activity, when based on the collectivity, stands up for: scientific knowledge, organization of teaching and sufficient relations. Therefore, the thesis defended in this paper, taking into consideration that the participants, when act based on reference of group work with characteristics of collectivity, are in a process of signification of their formation based on the essential relations that guide their actions in the project that is constituted as an activity.